محددات التضخم في الجزائر خلال الفترة 2000-2015 - رايس, فضيل (Recherches économiques et managériales, 2018)
يهدف هذا المقال إلى تحليل أهم مسببات الظاهرة التضخمية في الجزائر خلال الفترة 2000-2015 ، حيث تعتبر هذه الأخيرة جد معقد نظرا لتعدد وتداخل مسبباتها، بين أسباب نقدية وأسباب هيكلة، كما يساهم التضخم المستورد بشكل كبير في تفاقم هذه الظاهرة، كل هذا جعل أثارها عميقة ومكلفة، بالإضافة إلى أن تحميل سياسة بمفردها كالسياسة النقدية أو الموازنية مواجهة هذه المشكلة يعتبر تقصيرا كبيرا، ويستلزم الأمر صياغة سياسات على المستوى الكلي متناسقة فيما بينها تنتشل الإقتصاد الوطني من وضعية التخلف والركود التي يعيشها، وإستغلال موارده بالشكل الذي يجعل الإنتاج كافيا ومتنوعا . الكلمات المفتاحية : رقم قياسي لأسعار المستهلك، وضعية نقدية، تضخم مستهدف، صافي الأصول الخارجية . Summary : This article aims to analyze the most important causes of the inflationary phenomenon in Algeria during the period 2000 - 2015 Where the latter is considered a very complex due to the multiplicity and overlapping causes, between monetary causes and other structural, imported inflation also contributes significantly to the worsening of this phenomenon ,All this made its effects profound and expensive, in addition to the load on alone policy such as monetary policy or budgetary to face this problem is a major shortcoming, And it requires the formulation of consistent policies at the macro level to pull off the national economy and the status of underdevelopment and stagnation experienced by, and the exploitation of resources in the form that makes production enough and diverse and contributes to the stability of prices and the purchasing power of the national currency key words : consumer price index number CPI ,the monetary situation, Inflation target , net external. assets